A novel second near-infrared theranostic agent: a win–win strategy of tracing and blocking tumor-associated vessels for oral squamous cell carcinoma. (March 2022) - Wei, Z.; Zhang, H.; Zou, H.; Song, C.; Zhao, S.; Cao, Z.; Zhang, X.; Zhang, G.; Cai, Y.; Han, W.
Abstract: Tumor vessel co-option is a crucial predictor for tumor invasiveness but is easy to ignore in tumor vascular targeting therapy. A high density of tumor vessel co-option located alongside the tumor frontier predicted a high tendency of tumor invasion and regional metastasis. Herein, a novel second near-infrared (NIR-II) nanoagent (Coi8DFIC-sorafenib nanoparticles, CS NPs [CS NPs]) was constructed with an organic Coi8DFIC dye and sorafenib, which demonstrated high tissue penetration and low tissue autofluorescence, enabling imaging of vessel co-option and tumor micrometastasis. This nanotherapeutic agent displayed considerably improved quantum yield of fluorescence (0.89%), high reactive oxygen species (ROS) generation, and fairly good biosafety in vivo . Compared with indocyanine green (ICG), CS NPs exhibited better photostability and photothermal conversion efficiency. By tracking tumor-associated vessels and real-time tumor imaging, CS NPs could open/stop vascular targeting therapy by laser on/off. The combination of vessel disruption and imaging-guided photothermal therapy/photodynamic therapy provided a win–win strategy for oral squamous cell carcinoma.